Dapagliflozin protects against nonalcoholic steatohepatitis in db/db mice - Panshuang Qiao; Yingli Jia; Yingli Jia; Ang Ma; Jinzhao He; Chen Shao; Xiaowei Li; Shuyuan Wang; Baoxue Yang; Hong Zhou (Frontiers Media S.A., 2022)
Nonalcoholic fatty liver disease (NAFLD), which is the most common liver disease, is associated with type 2 diabetes mellitus and metabolic syndrome. Although there is no consensus on the treatment of NAFLD, growing evidence suggests that tight glycemic control would contribute to the improvement of NAFLD. However, some insulin sensitizers cannot improve NAFLD, especially nonalcoholic steatohepatitis (NASH). Whether insulin-independent hypoglycemic drug dapagliflozin, a sodium-glucose cotransporter-2 inhibitor, may improve NAFLD keeps unclear. Therefore, 12-week-old male C57BL/6 wild-type and db/db mice were treated with 1 mg/kg dapagliflozin or vehicle for 12 weeks. Dapagliflozin alleviated NASH, manifesting as decreased alanine aminotransferase and NAFLD activity score in db/db mice. Also, dapagliflozin reduced de novo lipogenesis by the upregulation of FXR/SHP and downregulation of LXRα/SREBP-1c in the liver of db/db mice. Moreover, dapagliflozin treatment reduced inflammatory response by inhibiting the NF-κB pathway and alleviated fibrosis by restoring the balance between fibrogenesis and fibrolysis in the liver of db/db mice. In summary, dapagliflozin alleviates NASH mostly by reducing lipid accumulation, inflammation, and fibrosis. These findings provide new insights for understanding the protective effect of dapagliflozin in NASH and suggest that dapagliflozin may be used to treat NASH.